A proanthocyanidin-rich extract from Cassia abbreviata exhibits antioxidant and hepatoprotective activities in vivo. (1st March 2018) - Sobeh, Mansour; Mahmoud, Mona F.; Abdelfattah, Mohamed A.O.; Cheng, Haroan; El-Shazly, Assem M.; Wink, Michael
Abstract: Ethnopharmacological relevance: Cassia abbreviata is a small to medium sized branched umbrella-shaped deciduous tree. It is widely spread in the tropics, especially in Africa, having a long history in traditional medicine for the treatment of numerous conditions such as headaches, diarrhea, constipation, some skin diseases, malaria, syphilis, pneumonia, stomach troubles, uterine pains, and against gonorrhea. Aim of the study: We investigated the phytochemical constituents of a root extract from Cassia abbreviata using HPLC-PDA-ESI-MS/MS. We also determined the antioxidant activities in vitro and in vivo using the nematode Caenorhabditis elegans as a model organism. The hepatoprotective activities in case of D-galactosamine (D-GaIN)-induced hepatotoxicity were studied in a rat model. Materials and methods: HPLC-PDA-ESI-MS/MS analysis allowed the identification of the secondary metabolites of the methanol extract. DPPH and FRAP assays were used to determine the antioxidant activities in vitro . Using the C. elegans model, survival rates under juglone induced oxidative stress, intracellular ROS content, quantification of Phsp-16.2 : GFP expression and subcellular DAF-16: GFP localization were investigated to determine the antioxidant activities in vivo . The in vivo hepatoprotective potential of the root extract was evaluated for D-galactosamine (D-GaIN)-induced hepatotoxicity in rats. The activity of the liver enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyltransferase (GGT), in addition to liver peroxidation product malondialdehyde (MDA) and glutathione content (GSH), as well as albumin and total bilirubin concentration, were determined. A histopathological study was also performed. Results and conclusions: C. abbreviata root extract is rich in polyphenolics, particularly proanthocyanidins. HPLC-PDA-ESI-MS/MS analysis resulted in the identification of 57 compounds on the bases of their mass spectra. ( epi )-Catechin, ( epi )-afzelechin, ( epi )-guibourtinidol, and ( ent )-cassiaflavan monomers as well as their dimers, trimers, and their diastereomers are the main components of the extract. The total phenolic content amounted for 474 mg/g root extract expressed as gallic acid equivalent using the Folin-Ciocalteu method. The extract exhibited powerful antioxidant activity with EC50 of 6.3 μg/mL in DPPH and 19.15 mM FeSO4 equivalent/mg sample in FRAP assay. In C. elegans model, the extract (200 μg/mL) was able to increase the survival rate by 44.56% and reduced the ROS level to 61.73%, compared to control group. Pretreatment of rats with 100 mg extract/kg (b. wt.) reduced MDA by 47.36% and elevated GSH by 59.1%. The extract caused a significant reduction of ALT, AST and GGT activities by 11%, 35.7% and 65%, respectively. The findings of this study suggest that the proanthocyanidin-rich extract from C. abbreviata may be an interesting candidate for hepatoprotective activity in case of hepatocellular injury. Graphical abstract: